APLIKASI KOAGULAN ALAMI DARI TEPUNG JAGUNG DALAM PENGOLAHAN AIR BERSIH - Eka Prihatinningtyas (Jurnal Teknosains, 2013)
Maize can be used as natural coagulant in water treatment process.The aim of this research was find the optimum condition on water treatment using natural coagulant from maize. Maize extract made by dissolving 5 grams of maize into 100 ml NaCl. The solution separated by centrifugation. The supernatant named extract of maize. Extract of maize loaded onto column packed with Amberlite and produced ionic maize.The active components are carboxyl, hydroxyl and amides groups. Ionic maize yield better turbidity removal than extract of maize. Coagulation withh high initial turbidity gave high efficiency of turbidity removal than low turbidity. Coagulation process runs efficiently at pH 5 because at that point the isoelectric point was obtained. The flowrate less than 0.03 m/ min, the alum will provide the efficiency of suspended solids removal greater than extract of maize. While the over flowrate higher than 0.03 m / min, settling velocity of kaolin using alum and extract of maize are the same.